2012
DOI: 10.1155/2012/197309
|View full text |Cite
|
Sign up to set email alerts
|

The Antitumor Activity ofAntrodia camphoratain Melanoma Cells: Modulation of Wnt/β-Catenin Signaling Pathways

Abstract: Antrodia camphorata (AC) is well known in Taiwan as a traditional Chinese medicine. The aim of this study was to investigate whether a fermented culture broth of AC could inhibit melanoma proliferation and progression via suppression of the Wnt/β-catenin signaling pathway. In this study, we observed that AC treatment resulted in decreased cell viability and disturbed Wnt/β-catenin cascade in B16F10 and/or B16F1 melanoma cells. This result was accompanied by a decrease in the expression of Wnt/β-catenin transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 53 publications
3
20
0
Order By: Relevance
“…Hence, disruption of Wnt/β-catenin signaling represents an opportunity for rational cancer chemoprevention and therapy[50].In agreement with this current work, our results showed that miR27a, FZD7 and Wnt/β-catenin certainly constitute a regulatory circuit that may be disrupted in HCC cells. Firstly, miR-27a alteration reduced the expressions of FZD7, β-catenin and MDR1/P-gp.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Hence, disruption of Wnt/β-catenin signaling represents an opportunity for rational cancer chemoprevention and therapy[50].In agreement with this current work, our results showed that miR27a, FZD7 and Wnt/β-catenin certainly constitute a regulatory circuit that may be disrupted in HCC cells. Firstly, miR-27a alteration reduced the expressions of FZD7, β-catenin and MDR1/P-gp.…”
supporting
confidence: 91%
“…However, multiple drug resistance (MDR) 46 constitutes a dominating clinical obstacle to successful treatment in HCC patients [2]. One of the common forms of MDR is caused by activa- 48 tion of the MDR1 gene, resulting in overexpression of P-glycoprotein 49 (P-gp) and conferring cancer cell resistance to a broad range of struc- 50 turally and functionally diverse chemotherapeutic drugs [3,4]. But so ation, and apoptosis [5,6].…”
mentioning
confidence: 99%
“…Lycogen™ are available from Asia-Pacific Biotech Developing, Inc. (Kaohsiung, Taiwan). Murine B16F10 cells are cultured in Dulbecco’s modified Eagle’s medium containing 10% fetal bovine serum, 1% glutamine and 50 μg/mL gentamicin at 37 °C in 5% CO 2 [11,12]. Adult zebrafish were obtained from a commercial dealer, and 10–15 fishes were kept in a 5 L acrylic tank with the following conditions; 28.5 °C, with a 14/10 h light/dark cycle.…”
Section: Methodsmentioning
confidence: 99%
“…From one side, the fabric itself hosts the bacteria acting as a medium between the human organism and the microorganisms; on the other hand, it is regarded as a well assessed tool for drug delivery in contact of skin for external applications [24][25][26]. Therefore wide market sectors push textile industries to concentrate more on antibacterial fabrics manufacturing to improve fabrics quality and product sales.…”
Section: Introductionmentioning
confidence: 99%